The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/ceat.200600394
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer Coefficients in Mechanically Agitated Gas‐Liquid Contactors

Abstract: There are a large number of correlations given in literature for the prediction of volume-related liquid-side mass transfer coefficients in mechanically agitated gasliquid contactors. Significant disagreement can be observed concerning the proposed correlations, so that no single correlation exists representing all of the mass transfer data given in the literature. The observed differences can mainly be ascribed to the differences in the geometry of the system, the range of operational conditions and the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 43 publications
(60 reference statements)
4
22
0
Order By: Relevance
“…We used the classical correlation based on the theory of isotropic turbulence using the power consumption per liquid volume and the superficial gas velocity to compare our experimental data. 27,[30][31][32][33][34][35] …”
Section: Correlationsmentioning
confidence: 99%
“…We used the classical correlation based on the theory of isotropic turbulence using the power consumption per liquid volume and the superficial gas velocity to compare our experimental data. 27,[30][31][32][33][34][35] …”
Section: Correlationsmentioning
confidence: 99%
“…Markopoulos et al (2007) compared the results which were obtained by other authors for agitated Newtonian and non-Newtonian aerated liquids. The comparative analysis carried out by Markopoulos et al (2007) shows that significant disagreement is observed taking into account the form of the correlations for k L a. Therefore, no single equation exists representing all of the mass transfer data given in literature.…”
Section: Survey Of the Results For Gas-liquid Systemmentioning
confidence: 93%
“…In literature, there are a large number of correlations for the prediction of volumetric mass transfer coefficients k L a in mechanically stirred gas-liquid systems (Linek et al, 1982(Linek et al, , 1987Nocentini et al, 1993;Gogate & Pandit, 1999;Vasconcelos et al, 2000;Markopoulos et al, 2007). Markopoulos et al (2007) compared the results which were obtained by other authors for agitated Newtonian and non-Newtonian aerated liquids. The comparative analysis carried out by Markopoulos et al (2007) shows that significant disagreement is observed taking into account the form of the correlations for k L a.…”
Section: Survey Of the Results For Gas-liquid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing the low impact of surface tension and seeking generalization, the mass transfer data obtained for STR in surfactin was correlated by the simplified power correlation [26],…”
Section: Experiments With a Fluid Foil Impellermentioning
confidence: 99%